Penerapan Produk Pembiayaan Perbankan dalam Prespektif Hukum Islam (Perbankan Syariah) - Irfan Ridha; Anisa Ayu Putri; Arina Putri Agustina; Ari Naldi; Ayu Saputri; Annisa Mardiya Hakim; Ahmad Kalingga; Aisyah Putri Indra; Alfajar Ahmad Abujibril; Bintang Reynaldo Putra; Alisha Zahra Saadiya (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This journal examines the implementation of banking financing products within the framework of Islamic law, focusing on the principles and practices of Islamic banking. The study explores how Islamic banking products align with Shariah principles, emphasizing compliance with prohibitions such as riba (usury), gharar (uncertainty), and maysir (gambling). The analysis also references the legal framework governing Islamic banking in Indonesia, particularly Law No. 21 of 2008 on Islamic Banking, and the regulations issued by the Financial Services Authority (OJK). The study evaluates the role of Islamic banks in promoting economic justice, financial inclusivity, and sustainable development. The findings aim to provide a comprehensive understanding of how Islamic finance products contribute to economic growth and the challenges faced by Islamic banking institutions in Indonesia’s financial market.